2017
DOI: 10.1097/md.0000000000008466
|View full text |Cite
|
Sign up to set email alerts
|

A giant and extensive solitary Peutz–Jeghers-type polyp in the antrum of stomach

Abstract: Rationale:A solitary Peutz–Jeghers-type polyp is a hamartomatous polyp which without either mucocutaneous pigmentation or a family history of Peutz–Jeghers syndrome (PJS). It can occur in all of the gastrointestinal tract, but it is extremely rare in the stomach.Patient concerns:A 53-year-old man was admitted to the local hospital with left upper abdominal pain lasting 2 weeks. A gastroscopy showed a giant and extensive bulging lesion on the greater curvature and posterior and anterior walls of the gastric ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Individuals with Peutz–Jeghers syndrome are at increased risk of different types of malignancies, such as gynecological, GI, and pancreaticobiliary carcinomas [ 13 ]. On the other hand, the malignant potential of SPJP is controversial [ 14 ]. Initial studies in the early 2000s suggested a benign course [ 15 ]; however, subsequent studies have contradicted the initial thoughts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with Peutz–Jeghers syndrome are at increased risk of different types of malignancies, such as gynecological, GI, and pancreaticobiliary carcinomas [ 13 ]. On the other hand, the malignant potential of SPJP is controversial [ 14 ]. Initial studies in the early 2000s suggested a benign course [ 15 ]; however, subsequent studies have contradicted the initial thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies in the early 2000s suggested a benign course [ 15 ]; however, subsequent studies have contradicted the initial thoughts. There have been cases that reported an association between SPJS with different malignancies [ 14 ]. Another study looked at the genetic and epigenetic analysis of colonic SPJP and detected epigenetic mutations similar to the mutations seen in colorectal cancer [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…that measured 110 mm × 80 mm × 4 mm in 2017. [ 6 ] Both the cases were adults, and they were reported in a 53-year-old male and a 43-year-old female, respectively. It is worth noting that a giant gastric polyp in PJS is extremely rare, and to our belief, this is the first case being reported from the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…were the first to report endoscopic submucosal resection for a giant solitary gastric polyp in PJS. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported risk for neoplastic transformation, SGHPs are generally referred for resection. 4 , 5 ESD may be an alternative to surgery for selected cases. We recommend close postoperative monitoring as delayed perforation can occur after large resections, and prompt recognition and intervention can prevent peritonitis and need for surgery.…”
mentioning
confidence: 99%